Tobacco Risk Information and Comparative Risk Assessment of E-Cigarettes Vs. Cigarettes: Application of the Reinforcing Spirals Model. Issue 4 (3rd April 2019) - Jun, Jungmi; Kim, Sei-Hill; Wu, Linwan
Abstract : We examine how individuals seek information about e-cigarette risk and selectively expose themselves to media sources that may provide information consistent with their existing beliefs and behaviors related to e-cigarettes in application of the Reinforcing Spirals Model (Slater, 2007). Additionally, the associations among e-cigarette risk information-seeking, tobacco risk information exposure via media, and comparative risk assessment of e-cigarettes versus conventional cigarettes were identified. The results were compared among current users, former users, and those who had never used e-cigarettes ("never users"). A nationally representative data from the 2017 Health Information National Trends Surveys - FDA was employed. Our analyses suggest the presence of comparative risk perception among current users as assessing the health harm and addiction risk of e-cigarettes significantly lower than cigarettes. Current users did not avoid information about the health effects of e-cigarettes; they were more likely to look for such information than former and never users. Current users' e-cigarette risk information-seeking was negatively associated with the difference between perceived addiction risk of e-cigarettes and that of cigarettes. Current users' tobacco risk information exposure via social media was related with a lower level of the perceived risk of e-cigarettes, while such exposure via news media was related with a higher level of perceived risk of e-cigarettes. Our findings suggest the need for regulating and counteracting the prevalent e-cigarette information that discounts the relative risks of e-cigarettes as well as the potential of news media as influential sources helping current users scrutinize the risks.